2013
DOI: 10.1523/jneurosci.3081-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Application of High-Frequency Repetitive Transcranial Magnetic Stimulation to the DLPFC Alters Human Prefrontal–Hippocampal Functional Interaction

Abstract: Neural plasticity is crucial for understanding the experience-dependent reorganization of brain regulatory circuits and the pathophysiology of schizophrenia. An important circuit-level feature derived from functional magnetic resonance imaging (fMRI) is prefrontalhippocampal seeded connectivity during working memory, the best established intermediate connectivity phenotype of schizophrenia risk to date. The phenotype is a promising marker for the effects of plasticity-enhancing interventions, such as high-freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
73
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 46 publications
2
73
1
Order By: Relevance
“…One hypothesis is that in the current study VLPFC stimulation after word offset interfered with post-stimulus episodic binding through an indirect effect on medial temporal lobe structures. In this respect, one should note that while the depth of TMS prevents a direct stimulation of these brain regions, recent studies have shown that PFC stimulation can modulate network dynamics and propagate to distant brain regions, including the hippocampus (Li et al, 2004;Bilek et al, 2013). Our findings could also be consistent with the notion of episodic buffer, a multidimensional storage system that provides a temporary interface between working memory and long-term memory by integrating information from different sources into a unitary episodic representation (Baddeley, 2000).…”
Section: Discussionsupporting
confidence: 84%
“…One hypothesis is that in the current study VLPFC stimulation after word offset interfered with post-stimulus episodic binding through an indirect effect on medial temporal lobe structures. In this respect, one should note that while the depth of TMS prevents a direct stimulation of these brain regions, recent studies have shown that PFC stimulation can modulate network dynamics and propagate to distant brain regions, including the hippocampus (Li et al, 2004;Bilek et al, 2013). Our findings could also be consistent with the notion of episodic buffer, a multidimensional storage system that provides a temporary interface between working memory and long-term memory by integrating information from different sources into a unitary episodic representation (Baddeley, 2000).…”
Section: Discussionsupporting
confidence: 84%
“…In parallel, altered functional plasticity processes, such as long-term potentiation, which form the molecular basis of learning and memory, are disrupted in animal genetic and behavioral models of schizophrenia (14,31). Our data add to a growing body of genetic, structural, and functional evidence implicating perturbed synaptic plasticity processes in altered prefrontal network dynamics observed in schizophrenic patients (3,34). A study of cortical thickness in patients with schizophrenia found decreases in the structural connectivity of the left and right DLPFC to be correlated with poor WM performance (36).…”
Section: Resultsmentioning
confidence: 57%
“…A well-established imaging genetics phenotype is functional connectivity between the right dorsolateral prefrontal cortex (DLPFC) and the left hippocampus (HC) during working memory (WM) performance (2)(3)(4). Specifically, impaired interaction of the HC and prefrontal cortex (PFC) has been proposed as a core abnormality during neurodevelopment in schizophrenia.…”
mentioning
confidence: 99%
“…At this time, the $64,000 question is what part of the brain should be stimulated with a global HDAC inhibitor on board to enhance synaptic efficacy and improve behavioral outcomes. It is reasonable to hypothesize that skill acquisition post-stroke in the rehabilitation setting will be enhanced with class I HDAC inhibition (that includes HDAC2) and noninvasive cortical stimulation of the hippocampal region locally, using deep penetrating magnetic fields (TMS) or focused transcranial electric fields, or indirectly via frontal cortex-hippocampus circuits using a frontal cortex target [57]. It is also reasonable to propose that motor learning might be enhanced by HDAC inhibitors only under conditions where stimulation of the motor cortex or experience are invoked.…”
Section: Neuroplasticity: Hebbian Plasticity and Carry-over In The Rementioning
confidence: 99%